Journey of the pharaohs [compact disc, unabridged] - Cussler, Clive; Brown, Graham, 1969- (Cussler, Clive. Kurt Austin adventure (Penguin Audio (Firm)), 2020)
The world's sea levels are rising, much higher than could be accounted for by glacier melt. Kurt Austin, Joe Zavala, and the rest of the NUMA team rocket around the globe in search for answers.